Pelatihan Pemanfaatan ChatGPT untuk Meningkatkan Literasi Digital UMKM Ibu-Ibu PKK di Kecamatan Rakit, Kabupaten Banjarnegara - Budi Wicaksana, Prasetyo; Randikaparsa, Irawan; Nuryana Fatchan, Ilham; Pramurindra, Rezky; Rimdang Kusuma, Hasna (Lembaga Pengembangan Kinerja Dosen, 2025)
Micro, Small, and Medium Enterprises (MSMEs) managed by PKK women in Rakit District, Banjarnegara Regency, still face limitations in utilizing digital technology, particularly in supporting marketing and business communication activities. Low digital literacy and limited assistance have become major challenges in optimizing the role of PKK in community economic empowerment. This community service program aims to enhance the digital literacy of PKK women’s MSMEs through training and assistance in using ChatGPT as a business marketing support tool. The methods employed include pre-test, material presentation using PowerPoint, hands-on practice in using ChatGPT, and post-test as an evaluation tool. The results indicate an improvement in participants’ understanding after the training, as reflected by higher post-test scores compared to pre-test scores among all participants. Furthermore, participants were able to produce simple product descriptions and promotional content relevant to their respective businesses. These findings suggest that ChatGPT can serve as a practical solution to improve digital literacy and support MSME management and marketing at the local level.